High-resolution mapping of in vivo genomic transcription factor binding sites using in situ DNase I footprinting and ChIP-seq - Chumsakul, Onuma; Nakamura, Kensuke; Kurata, Tetsuya; Hobman, Jon L.; Ogasawara, Naotake; Oshima, Taku; Ishikawa, Shu (Oxford University Press, 2013)
Accurate identification of the DNA-binding sites of transcription factors and other DNA-binding proteins on the genome is crucial to understanding their molecular interactions with DNA. Here, we describe a new method: Genome Footprinting by high-throughput sequencing (GeF-seq), which combines in vivo DNase I digestion of genomic DNA with ChIP coupled with high-throughput sequencing. We have determined the in vivo binding sites of a Bacillus subtilis global regulator, AbrB, using GeF-seq. This method shows that exact DNA-binding sequences, which were protected from in vivo DNase I digestion, were resolved at a comparable resolution to that achieved by in vitro DNase I footprinting, and this was simply attained without the necessity of prediction by peak-calling programs. Moreover, DNase I digestion of the bacterial nucleoid resolved the closely positioned AbrB-binding sites, which had previously appeared as one peak in ChAP-chip and ChAP-seq experiments. The high-resolution determination of AbrB-binding sites using GeF-seq enabled us to identify bipartite TGGNA motifs in 96% of the AbrB-binding sites. Interestingly, in a thousand binding sites with very low-binding intensities, single TGGNA motifs were also identified. Thus, GeF-seq is a powerful method to elucidate the molecular mechanism of target protein binding to its cognate DNA sequences.